DEVELOPMENT OF DATA PROCESSING SOFTWARE FOR RAILROAD MEASUREMENT RESULTS AND TQI CALCULATIONS FOR SEMI-HIGH SPEED TRAIN THROUGH TRAIN DYNAMIC RESPONSE ANALYSIS - Rifky Abyan, Muhammad
Railway transportation in Indonesia has grown rapidly. This can be seen by the existence of Jakarta – Surabaya semi-high speed train project. In order to operate properly, railway trains need railroads with a Track Quality Index (TQI) value that meets the standards of PT Kereta Api Indonesia (KAI). However, TQI of KAI standard has several problems. First, TQI of KAI standard does not cover the operating speed of semi-high speed train. Second, TQI of KAI standard is calculated with the standard deviation of track irregularities in a certain segment. This has the potential to cause local segments of rail roads that no longer feasible to use to go unnoticed. Starting from these problems, in this study two software was developed to evaluate the problems that have been mentioned. The first software is a software to restore track irregularities data. These data are then used to obtain railway train dynamic responses through dynamic simulation. The railway train dynamic responses are analyzed to acquire the recommended TQI of KAI standard for semi-high speed train. The second software is a software to assess the quality of railroads based on 3 standards, which are TQI of KAI standard and BS EN 13848 standard . The results of this software are then used to perceive the adequacy of TQI of KAI standard by comparing it with the other standard. From the results of the analysis of the railway train dynamic responses, it was found that the recommended value of TQI for semi-high speed train is between 7 – 12. Meanwhile, the comparison with BS EN 13848 standard show that TQI of KAI standard is feasible to use, but assessment by maximum deviation for each railroad geometry parameter must also be carried out.